2010
DOI: 10.1259/dmfr/147454468
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of demineralized bone and bone transplantsin vitroandin vivowith cone beam computed tomography imaging

Abstract: Both the KaVo 3DeXam and Morita 3D Accuitomo devices produce good-quality images of cancellous bones in in vivo remodelling as well as after in vitro demineralization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Draenert et al (24) stated that the OsiriX software is able to produce good-quality images of cancellous bones in their in vivo and in vitro study. After comparison among similar software, Yamauchi et al (25) considered OsiriX a highly functional DICOM viewer, which is an important tool for preoperative planning in spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Draenert et al (24) stated that the OsiriX software is able to produce good-quality images of cancellous bones in their in vivo and in vitro study. After comparison among similar software, Yamauchi et al (25) considered OsiriX a highly functional DICOM viewer, which is an important tool for preoperative planning in spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Chindasombatjareon reported the same in both CT and CBCT [ 27 ]. Another studies found an inverse correlation between the severity of metal artifact and applied voltage [ 28 , 29 ]. The majority of photons have medium level of energy and a small number of photons have maximum energy [ 5 , 12 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though multi-slice CT (MSCT) scan is an established method to assess the bone morphology in implant planning and is commonly regarded as the gold standard, it is associated with 40-60 times more radiation than CBCT systems that have been introduced more recently. In addition to lower dose of exposure, CBCT systems offer several other advantages over a medical CT, including shorter acquisition times, low cost, and adequate image quality of the mineralized tissues (17,18). Different studies have utilized various techniques using CBCT to approximate defects, but no study has directly compared these techniques.…”
Section: Discussionmentioning
confidence: 99%